1993
DOI: 10.1111/j.1464-410x.1993.tb16219.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transurethral Resection of Prostate on Plasma Hormone Levels in Benign Prostatic Hyperplasia

Abstract: Circulating levels of pituitary and adrenal hormones were measured in patients with benign prostatic hyperplasia before and after transurethral resection of the prostate (TURP). TURP caused a significant increase in plasma LH levels 2 weeks and 3 weeks after surgery. The plasma prolactin level decreased significantly 3 weeks after prostatectomy but plasma concentrations of FSH and ACTH were unchanged. TURP did not alter circulating levels of aldosterone, cortisol, DHEA-S and testosterone. These data suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…Rolandi et al [14], however, have been able to show that prolactin levels could decrease following prostatectomy. Similar results have been observed after TURP on days 14 and 21 [7].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Rolandi et al [14], however, have been able to show that prolactin levels could decrease following prostatectomy. Similar results have been observed after TURP on days 14 and 21 [7].…”
Section: Discussionsupporting
confidence: 79%
“…This alteration was again significant with respect to the values observed in control patients [7]. In our study, a significant alteration in plasma LH levels has been observed in patients undergoing TURP during the 3 weeks' follow-up.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The immediate anatomic cause of the disease is enlargement of the paraurethral prostate gland. The pathogenesis remains unclear [10, 11], although hormonal disorders definitely play a major role [12, 13]. …”
Section: Introductionmentioning
confidence: 99%